Investigation of structural, magnetic, and magnetocaloric properties of nanocrystalline double perovskite Pr2CoMnO6. (29th June 2018) - Rawat, Khemchand; Meenakshi; Mahato, Rabindra Nath
Abstract: We have investigated the structural, magnetic, and magnetocaloric properties of the nanocrystalline double perovskite Pr2 CoMnO6 oxide prepared by the sol-gel method. The x-ray diffraction (XRD) using Rietveld refinement shows that the sample under investigation crystallizes into the orthorhombic crystal structure with Pbnm space group. The average crystallite size calculated using Debye-Scherer's formula was found to be ∼17 nm. The scanning electron microscopy image shows that the particles formed were of almost uniform in size with particle size ∼192 nm. The temperature dependence magnetization data shows that sample has a paramagnetic to ferromagnetic phase transition around 173 K. A series of M-H isotherms were performed at a gap of 10 K around transition temperature. The maximum entropy change (∣ΔSmax ∣) was found to be 1.98 Jkg −1 K −1 at a field change of 5 T and relative cooling power (RCP) was calculated to be 110 J kg −1 . These obtained values are reasonably high and could be the potential material for magnetic refrigeration technology.